A Substrate Current Less Control Method for CMOS Integration of Power Bridges. (17th August 2010) - Krupar, Joerg; Hauswald, Heiko; Naumann, Ronny
Abstract : Modern electronical devices use high integration to decrease device size and cost and to increase reliability. More and more devices appear that integrate even power devices into VLSI circuits. When driving inductive loads, this is a critical step because freewheeling at a power device appears. In these applications usually special technologies with extra wells for the power devices, SOI technologies, or BiCMOS technologies are required to suppress any substrate current. However, the use of these technologies results in higher production cost for the device. We present a method to control the freewheeling actively. Using this approach we are able to integrate the power devices using a normal CMOS technology.